Competition policy in Ireland: A good recession? - Paul K. Gorecki (The Economic and Social Research Institute (ESRI), 2012)
This paper analyses the conduct of competition policy in Ireland between 2000 and 2011. Attention is paid to the policies and actions of those persons and institutions responsible for competition policy: the Minister for Jobs, Enterprise and Innovation; the Competition Authority; the Courts; and, since 2010, the European Union and the International Monetary Fund. Competition policy after some initial setbacks at the beginning of the recession, has enjoyed strong support since 2010.
Keywords: 330